Priložnosti in izzivi vezani na novo skupino zdravil (zaviralci PCSK9) za zniževanje holesterola LDL - Locatelli, Igor (Farmacevtski vestnik, 2016)
PCKS9 inhibitors represent a new therapeutic target for hypercholesterolemia treatment. Monoclonal antibodies have been most extensively studied in clinical trials. Among them evolocumab and alirocumab were approved for use in summer 2015. They can be used as add-on therapy to inefficient standard hypercholesterol treatment or as monotherapy when standard treatment is contraindicated or intolerant. In clinical trials on evolucumab or alirocumab the LDL cholesterol was additionally reduced by approximately 50% in patients with primary hypercholesterolemia. At the moment, there are limited data on clinical impact of these medicines such as the cardiovascular event rate reduction. Patients with the highest risk of cardiovascular event having inefficient standard hypercholesterol treatment will benefit most from these medicines. These patients include patients with familial hypercholesterolemia or patients with cardiovascular disease and additional risk factors (e.g. diabetes) or patients with statin intolerance with elevated LDL cholesterol level.
Keywords: alirokumab; družinska hiperholesterolemija; evolokumab; PCSK9; statinska intoleranca